Using the 9-BBN Group as a Transient Protective Group for the Functionalization of Reactive Chains of α-Amino Acids - Sánchez, Adrián; Calderón, Ernesto; Vazquez, Alfredo (Synthesis, 2013)
Achieving chemoselectivity is a longstanding challenge in chemical synthesis. This problem has been addressed using different approaches, but a definitive solution is still pending. For instance, in peptide chemistry, particularly with amino acids containing side chains functionalities with reactivity patterns similar to the main functional groups, such as aspartic and glutamic acids, and lysine and ornithine, specific semi-permanent protecting groups have been employed. The use of 9-borabicyclo[3.3.1]nonane (9-BBN-H) as a transient protective group for the selective protection of α-amino acids, which allows the chemoselective manipulation of the functional groups embedded in the side chains of the molecule, is described.
Keywords: α-amino acids; selective protection; 9-BBN-H; protecting groups; oxazaborolidinones